Prolactin as a Candidate Gene Controlling Molting and Egg Production of Duck - Triana Susanti (Indonesian Center for Animal Research and Development, 2015)
Incidence of molting is a crucial problem in the local ducks that need to be handled from many aspects including genetic aspect. Handling of molting genetically can be done quickly and accurately when the control genes have been found. The search for marker genes of molting can be conducted in poultry through broodiness naturally, because its physiological processes are related to the continuity of egg production. This paper describes the mechanism of molting, the relationship of molting with prolactin hormone and the association of prolactin gene polymorphism with molting and egg production. Molting and egg production were influenced by the prolactin hormone, that may be controlled by the prolactin gene. High concentration of prolactin hormone will inhibit the function of pituitary gland, decreasing production of gonadotrophin hormone (follicle stimulating hormone and luteinizing hormone) hence ovulation ceased. This will stop egg production and at the same time molting proccess occurred. Key words: Prolactin gene, molting, egg production, duck